Historyczne i konstytucyjne korzenie niestabilności rządów we Włoszech - Lai, Luigi (PRAWO i WIĘŹ, 2026)
This paper analyses the historical and constitutional origins of Italian government instability, demonstrating the relationship between the “pure” parliamentary model adopted in the 1948 Constitution and its systemic and political ramifications. The author outlines the evolution of the Italian state system and the relationship between parliament and the government, as well as the role of the president of the republic, in the context of the absence of mechanisms for parliamentary rationalisation. The paper also draws comparisons between Italy and other European systems, particularly Poland and Germany, to identify sources of greater institutional stability. Finally, the paper reflects on contemporary proposals for constitutional reform, considering the balance between the rule of law and democratic representation.